Digital Healthcare and Pharmacy Practice: The Impact of Telepharmacy on Patient Outcomes and Medication Adherence - Al-Ghamdi, Fuad; Dobayan, Zakariya Al; Abushoumi, Fatimah.; Ahmed Khazi, Anees; T S, Abdul Haseeb (Journal of Neonatal Surgery, 2025)
Telepharmacy has seen a paradigm shift in the form of pharmaceutical practice and has taken steps forward to provide a changing pattern of medication care and assistance to patients. The current review is a broad overview of the complex effects of telepharmacy on patient outcomes and the mode of patient enhancement, especially on medication adherence and clinical efficacy. With the help of modern evidence review and worldwide implementation approaches, we can look into the way digital health technology has changed the landscape of the pharmacy practice, allowing distant consultation, medication therapy management, and patient monitoring. The review systemates the evidences obtained in different contexts of medical practice that confirmed the ability of telepharmacy to overcome geographical distance, assist patient engagement, and maximize the effectiveness of therapy. There are both tremendous advantages, which can be observed, and ongoing challenges such as technological infrastructure, regulatory issues or implementation barriers, which persist and affect the adoption rates. In our analysis, we have seen that the telepharmacy concept can only enhance medication adherence rate, minimize adverse drug events, and elevate satisfaction levels of patients, especially those lacking healthcare facilities. These advantages are further extended by the use of artificial intelligence, mobile health platforms, and remote monitoring technologies, and allow the possibility of personalised, data-driven pharmaceutical care. The present review supplies evidence-based suggestions on healthcare policymakers, practitioners, and researchers who want to reengineer telepharmacy usage and make the most out of its potential to improve patient-centered care delivery in the digital age of healthcare..